(untitled) (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
This study aims to develop and evaluate a Visual Communication Design (VCD) strategy for online promotion through Facebook at CV. Cahaya Grafika in Demak. The research applied a design-based approach, combined with audience perception testing using a Likert-scale questionnaire distributed to 30 respondents aged 18–44 years. The development produced five main outputs: Facebook photo posts, profile and cover design, group posts, story-format content, and adaptation for printed banner media. The results show significant improvement in visual attractiveness, message clarity, brand recognition, and engagement performance. The findings indicate that systematic visual optimization enhances promotional effectiveness in both digital and print media.